1995
DOI: 10.1007/bf00298427
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients with prostatic cancer treated with orchidectomy and with estrogens

Abstract: Bone mineral density (BMD) and bone mineral content (BMC) were measured in the femoral neck area, trochanteric area and Wards triangle, and in the distal radius of the left forearm before and after 1 year of endocrine treatment in 27 patients with prostatic cancer. Eleven of the patients were treated with orchidectomy and 16 with combined oral and intramuscular estrogens. The patients were free from metastases during the entire observation period. In the orchidectomized patients, BMD and BMC of the distal radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(71 citation statements)
references
References 16 publications
2
68
0
1
Order By: Relevance
“…Maillefert et al found that, after 1 year of ADT, there was a 4.6% decrease in BMD at the lumbar spine and a 3.9% decrease at the femoral neck [13]. Orchiectomy also resulted in substantial changes, with a 15% decrease in trochanter BMD after 1 year reported in one study [25]. After 1 year of ADT, 15 men with adenocarcinoma of the prostate had significantly lower BMD at the total hip and ultradistal radius than age-and sex-matched controls.…”
Section: Unique Aspects Of Cancer Therapyassociated Bone Lossmentioning
confidence: 92%
“…Maillefert et al found that, after 1 year of ADT, there was a 4.6% decrease in BMD at the lumbar spine and a 3.9% decrease at the femoral neck [13]. Orchiectomy also resulted in substantial changes, with a 15% decrease in trochanter BMD after 1 year reported in one study [25]. After 1 year of ADT, 15 men with adenocarcinoma of the prostate had significantly lower BMD at the total hip and ultradistal radius than age-and sex-matched controls.…”
Section: Unique Aspects Of Cancer Therapyassociated Bone Lossmentioning
confidence: 92%
“…BMD significantly decreased in the patients who underwent orchiectomy but did not change in the estrogen group. Treatment was tolerated well in both groups [78]. More recent studies revisited estrogen therapy, given the better understanding of the importance of estrogens in bone metabolism.…”
Section: Osteoporosismentioning
confidence: 92%
“…As regards bone, oestrogens do not exhibit toxicity. This is because their use, as opposed to surgical orchiectomy or LHRH analogue use, does not have a significant lowering effect on bone density [77], and may even exhibit a protective action on bones [78]. LHRH analogues currently constitute an alternative -one widely used and preferred by patients -to surgical orchiectomy [79].…”
Section: Hormone Therapy In Prostate Cancermentioning
confidence: 99%